Improved space-time coding for MIMO-OFDM wireless communications. - Blum, R.S.
Improved space-time coding for multiple-input multiple-output orthogonal frequency division multiplexing is studied for wireless systems using QPSK modulation for four transmit and four receive antennas. A 256-state code is shown to perform within 3 dB of outage capacity (and within 2 dB with perfect channel estimation), which is better than any other published result without using iterative decoding
Keywords: 256-state code; MIMO-OFDM wireless communications; QPSK modulation; Multiple-input multiple-output system; Orthogonal frequency division multiplexing; Outage capacity; Perfect channel estimation; Receive antennas; Space-time coding; Transmit antennas